2021
DOI: 10.1111/anae.15587
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic training during the COVID‐19 pandemic

Abstract: The COVID-19 pandemic has dramatically impacted anaesthetic services and the delivery of anaesthetic training across the UK and internationally [1, 2]. Trainee case-load is thought to have been reduced during the pandemic by factors including: redeployment to critical care; cancellation of elective surgery; staff self-isolation, quarantine and shielding; and absences due to sickness. We sought to quantify the effect of these changes on anaesthetic training by exploring logbook data recorded by trainees before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…The initial impact of changes in case and procedural volumes on our program was primarily limited to the EP and R1 phases lasting a combined 10 weeks. The drop in case volume at UMMC and STC closely mirrored that reported in the US [ 28 ] and elsewhere [ 6 , 7 , 15 ]. The impact of the COVID-19 pandemic on our anesthesiology residents varied between trainees depending on what rotations they were scheduled to complete during the most heavily impacted pandemic phases.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The initial impact of changes in case and procedural volumes on our program was primarily limited to the EP and R1 phases lasting a combined 10 weeks. The drop in case volume at UMMC and STC closely mirrored that reported in the US [ 28 ] and elsewhere [ 6 , 7 , 15 ]. The impact of the COVID-19 pandemic on our anesthesiology residents varied between trainees depending on what rotations they were scheduled to complete during the most heavily impacted pandemic phases.…”
Section: Discussionsupporting
confidence: 83%
“…Trainees in anesthesiology and other specialties worldwide have been directly affected by common pandemic response measures and their sequelae. The potential consequences of the altered anesthesiology trainee experience have been reviewed [1][2][3][4][5][6][7]. One common, early, worldwide response measure was the cessation of nonemergent surgical cases to preserve resources, including personal protective equipment (PPE) and acute care hospital beds.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first study to assess the impact of the COVID-19 pandemic on anaesthesia training in Ireland. In comparison, the only other quantitative study published to date examining anaesthesia training during the pandemic found a 35% reduction in trainee theatre caseload from a UK logbook analysis 9 . Training data from Irish surgical specialties during the pandemic has demonstrated caseload reductions of approximately 20%, similar to our own findings 10 .…”
Section: Discussionmentioning
confidence: 79%
“… 6 This resulted in fewer opportunities for solo lists, reduced caseload, and decreased case mix for trainees. 7 , 8 Staff sickness, self-isolation, and cancellation of fellowships further limited subspecialty training for senior trainees. 3 , 7 In addition, clinical guidelines rapidly evolved during the pandemic, demanding clinicians to frequently update their knowledge.…”
mentioning
confidence: 99%
“… 7 , 8 Staff sickness, self-isolation, and cancellation of fellowships further limited subspecialty training for senior trainees. 3 , 7 In addition, clinical guidelines rapidly evolved during the pandemic, demanding clinicians to frequently update their knowledge. 9 COVID-19 also necessitated substantial changes in work pattern, the hospital landscape, resource allocation, and team structure.…”
mentioning
confidence: 99%